The Oxford Handbook of Iranian History: By Touraj Daryaee, ed. (New York: Oxford University Press, 2012. 398 pages.) (American Journal of Islam and Society, 2013)
Narrating the history of a nation from approximately 1,000,000 BCE to 2009CE in 389 pages is a daunting and noteworthy task undertaken by the scholarswho have contributed to The Oxford Handbook of Iranian History. This collectionof sixteen short essays by distinguished anthropologists, archaeologists,historians, and philologists of the Iranian world divides Iranian history intothree general periods: ancient, medieval, and modern. Chapters 1 to 7 addressthe ancient Iranian dynasties, chapters 8 to 13 talk about medieval Iran, andthe last three focus on modern Iran. In the words of editor Touraj Daryaee,each chapter has been written in a way to provide “comprehensive informationfor students at the university level and for the uneducated layperson” (p. ii).Therefore, the book is intended to be more of an introduction rather than areference book for scholarly research ...